Novel Synthesis of Macromonomers by Mechanochemical Reaction for the Application to Polymeric Micelles - Shin-ichi Kondo,; Masashi Tsukamoto,; Yasushi Sasai,; Yukinori Yamauchi,; Masayuki Kuzuya, (Journal of Pharmacy and Nutrition Sciences, 2011)
We have presented the first example of the synthesis of macromonomers by mechanochemical reaction of polymethylmethacrylate (PMMA) and maleic anhydride (MA). The mechanochemical reaction of PMMA and MA was carried out by vibratory ball milling under anaerobic condition. The ESR spectrum of the fractured sample of PMMA and MA showed a broad singlet, which was apparently different from the spectrum of PMMA mechanoradical. Therefore, PMMA mechanoradical would react with MA. We underwent the UV-labeling of the fractured samples of PMMA and MA to confirm the formation of macromonomers. The gel permeation chromatograms of UV-labeled compounds derived from this fractured sample showed a broad peak in a polymer region with refractive index detector and UV detector, which indicates that macromonomers bounding MA would be produced. This method seems to be applicable for a wide variety of polymers to synthesize macromonomers possessing MA.